PERKEMBANGAN KINERJA KEUANGAN BANK UMUM SYARIAH DI INDONESIA PADA TAHUN 2009-2014 - Sasmita Claudia Pontoh (Universitas Trunojoyo Madura, 2015)
Nowadays sharia commercial banks have grown. The purposes of this paper was to see the development of sharia commercial banks from 2009-2014. The development of the financial performance of sharia commercial banks in Indonesia were not thrive and impressed as stable and not increased. Financial ratios indicate that sharia commercial banks were not experiencing rapid growth. Total asset of sharia commercial banks have increased every year. Sharia commercial bank’s market share is 5% of the total assets of bank nationwide.